Management of chemotherapy induced emesis - Roila Fausto (Archive of Oncology, 2004)
Important progress has been achieved in the last few years in the prevention of chemotherapy-induced nausea and vomiting thanks to the introduction in clinical practice first of the 5-HT3 antagonists and of the NK1 antagonists more recently. To prevent acute emesis induced by cisplatin, moderately emetogenic chemotherapy, a combination of aprepitant plus a 5-HT3 antagonist and dexamethasone is now the most efficacious regimen. For the prevention of delayed emesis induced by cisplatin, moderately emetogenic chemotherapy, a combination of dexamethasone plus aprepitant or metoclopramide or a 5- HT3 antagonist / dexamethasone or a 5-HT3 antagonist are the preferred antiemetic regimens. For the prevention of acute emesis induced by low emetogenic chemotherapy a prophylaxis with a single antiemetic drug such as dexamethasone is suggested while no antiemetic prophylaxis should be administered to prevent acute emesis induced by minimal emetogenic chemotherapy or to prevent delayed emesis induced by low or minimal emetogenic chemotherapy. In this last case a rescue therapy should be administered in patients presenting acute or delayed emesis.